(untitled) (New York, 2003)
An activity-based approach to teaching with an emphasis on using manipulatives to build conceptual understanding! This invaluable book combines practical teaching ideas, updated assessment techniques, and the NCTM Assessment Standards to give teachers all the background they need to introduce elementary and middle school students to the wonders of mathematics.
Keywords: Mathematics,Mathematics,Toán học,Toán học; Study and teaching (Elementary),Study and teaching (Middle school),Học tập và giảng dạy (Sơ cấp, Tiểu học),Học tập và giảng dạy (Trung học)